Body Mass Index, Lipid profile and Cardiovascular diseases - Siddiqui, Imran Akhtar (Journal of Ayub Medical College Abbottabad, 2004)
This is with reference to an article titled Relation of body mass index with lipid profile and blood pressure in young healthy students at Ziauddin medical University by Javed Aziz published in the issue of J Ayub Med Coll Abbottabad 2003;15(4). I appreciate the author's efforts in performing a risk factor profile of CVD in young medical students. South Asians have been observed to have a higher prevalence of cardiovascular diseases (CVD) in all age groups1. Studies are lacking in the Pakistani population on both the CVD patients and normal population in terms of CVD risk factors. I have a few questions regarding the risk factor profiling that has been done and the use of statistics in this study. In this study, the authors have stratified the population on the basis of their Body Mass Index and have characterized their population as having normal weight and over weight on the basis of BMI. However some people classified as overweight might have a larger muscle mass. Thus a more specific marker that has been identified in increasing the risk for CVD is abdominal obesity which is defined separately for men and women. (Waist circumference greater than 40 inches in men and 35 inches in women)2. Clinical studies have noted a high correlation between abdominal obesity, lipid profiles, high blood pressure and fasting glucose 3,4. Thus a failure of correlation between lipid profiles and BMI in this study can be explained on the basis of the stratification of the population done. Smoking an important risk factor that is an independent risk factor for CVD and has been shown to lower HDL levels has not been looked in this study5. In addition gender can play as a confounding effect on the lipid profiles. Men have been shown to have earlier elevations of LDL cholesterol and blood pressure than Women6. Thus multivariate analysis with appropriate model selection should have been done. It was a good study and will open new research avenues but the results can be reanalyzed using abdominal obesity as a stratification marker, inclusion of smoking in the risk factor profile list and a multivariate approach to interpret the data.